A surface-subsurface model for the tecno-economic and risk evaluation of thermal EOR projects - Badar, Al-Abri (Cranfield University, 2011)
The global resources of unconventional oil such as heavy oil, extra-heavy oil, and bitumen are vast and are expected to play an increasingly important role in meeting the world‘s future energy needs. However, the highly viscous nature of these resources means that only a small fraction of them can be recovered by the simple and inexpensive primary and secondary oil recovery techniques. A greater fraction demands complex and costly tertiary oil recovery techniques known as Enhanced Oil Recovery (EOR). Of the various EOR techniques available today, the recovery of viscous oil remains inextricably tied to steam-based EOR (S-EOR). S-EOR involves the injection of large quantities of steam into the reservoir in order to reduce the oil viscosity to improve its mobility, and thus increase oil production. The economics of S-EOR projects is governed by the time-rate of the recovery of oil versus the time-rate of expenses required to recover this oil. Steam generation is typically the largest cost component in S-EOR projects and it accounts for more than fifty percent of the total operating cost. Despite this, the focus during preliminary development phases is often on maximizing the oil production rate rather than optimizing long run economics. It is argued throughout this study that for optimum S-EOR development, the decision-making process should be based upon optimizing the long term economics. A multidisciplinary approach that includes considerations of surface, subsurface, environmental, and risk perspectives is therefore needed. This thesis reports on the development of TERM-EOR, an integrated surface-subsurface tool to enhance the decision-making processes involved in S-EOR projects. The tool consists of economic, fiscal, environmental, and risk modules that are fully integrated in a single user-friendly platform. The tool can be used both during project feasibility studies and for operation optimization. The use of TERM-EOR is illustrated through two case studies, one of which is surface-oriented while the other is subsurface-oriented. In the first case study, the thermodynamic performance of gas turbine cogeneration in a typical S-EOR project is evaluated and its economics is compared with a fired boiler system. Cogeneration wasfound to provide substantial fuel savings and CO2 reduction, and its economics remains competitive even under the most unfavourable conditions. The unit technical cost (UTC) of the project with cogeneration was found to be between 2 to 10 dollars lower than the project without. In addition, the break-even oil price for the project with cogeneration was also found to be 6 to 8 dollars lower than that without. In the second case study, TERM-EOR is used to optimize the operating pressure of a Steam Assisted Gravity Drainage (SAGD) project. It was found that there is no cut-off answer to the question of optimum operating pressure for SAGD. The answer is found to be influenced by a number of factors including the obtained oil rate, the steam to oil ratio, crude oil prices, steam technology and steam cost, as well as the environmental regulations in place. Operating at high pressure, though resulting in higher oil rates, increases steam consumption, fuel usage and GHG emissions. On the other hand, operating at low pressure is thermodynamically more efficient but results in lower oil rates. In general, from a government viewpoint the economics of the SAGD project was found to be more sensitive to the obtained oil rate, and thus favouring high pressure operations. This is in contrast to the oil company perspective where the economics was found to be driven by the operating costs, and thus favouring low pressure operations. A preliminary thermodynamic evaluation of a parabolic-trough solar system designed to deliver steam for S-EOR projects was carried out. The study highlights a number of technical challenges facing the integration of solar technology into S-EOR operations. For a typical day in Oman, it was found that the steam injection process can only be maintained for less than nine hours a day, after which the steam injectors will be shut-in. The cyclic cooling and heating of injector wells will expose them to fatigue problems, which may result in premature failures. Solar-generated steam will also have to be injected at peak rates during daytime in order to compensate for steam unavailability during the night. The peak in steam rate for the solar case was found to be three times greater than that required for constant-rate operation. Therefore, more steam injectors and larger steam facilities with high turndown capabilities are required to handle peak steam rates. It will also raise concerns about the steam injectivity of the reservoir and whether it will be able to handle peak steam rates associated with solar steam plants, an issue which is still open to debate.